Determining the expression levels of CSF‐1 and OCT4, CREM‐1, and protamine in testicular biopsies of adult Klinefelter patients: Their possible correlation with spermatogenesis. (19th August 2022) - Abofoul‐Azab, Maram; Lunenfeld, Eitan; Kleiman, Sandra; Barda, Shimi; Hauser, Ron; Huleihel, Mahmoud
Abstract: Klinefelter syndrome (KS) is the most prevalent genetic disorder of infertile males. This study aimed to determine in Klinefelter patients (KS) the expression levels of spermatogenic markers and testicular growth factors that might predict spermatogenesis based on conventional testicular sperm extraction (TESE). The expression levels of the pre‐meiotic ( OCT4, CD9, GFR‐ α 1, α‐ 6‐INTEGRIN, SALL4, C‐KIT ), meiotic ( CREM ‐ 1 ), and post‐meiotic (protamine) markers, as well as the colony stimulating factor‐1 ( CSF‐1 ) were examined in testicular biopsies with and without mature sperm of KS and normal karyotype of azoospermic patients (AZO) with complete spermatogenesis. In the biopsies of AZO, the expression levels (fold of expression compared to the PPI of the same sample) of OCT4 were 9.68± 7.93, CREM 42.78± 28.22, CSF‐1 3.07 ± 3.19, and protamine 78498.12 ± 73214.40. Biopsies from KS included 7 with sperm and 17 without sperm. Among the biopsies with sperm, the expression levels of OCT4 were 7.27± 9.29, CREM 3.13± 7.89, CSF‐1 35.5 ± 48.01, and protamine 902.97 ± 2365.92. In 14 biopsies without sperm, we found low expression levels of OCT4, CREM and CSF‐1, and no expression of protamine. However, in three of the biopsies without sperm that highly expressed OCT4 and CSF‐1, the expression levels of CREM ‐1 and protamine were high. These results may be used for further consulting with patients considering repeating conventional TESE or micro TESE and cryopreservation for possible future in‐vitro spermatogenesis.